A study on digital transformation in the healthcare sector of Bangladesh: Current scenario and the future roadmap - Md. Mahfuzur Rahman Khan; M. Mehedi Hasnat Al Amin (Goodwood Publishing, 2021)
Purpose: This study investigates the essential characteristics of digitalization and transformation in the healthcare sector in Bangladesh. It also examines the correlation between digital technology and developing factors in the current healthcare system and recommendations to overcome the crises still dwelling within the healthcare framework. Research methodology: To gain a more vital understanding of the underlying insights of Digital Transformations of the healthcare sector of Bangladesh, the authors decided to conduct explorative research in qualitative format. Results: As a developing country with increased economic solvency, Bangladesh is enduring a metamorphosis in medicine & healthcare. Despite inequity in digital-initiated “equality,” developing healthcare systems worldwide are getting in touch with digital technology. Limitations: There are shortcomings in theoretical research as the previous practice of pedagogues and learners is challenged by new-age communication and the healthcare system based on digital technology. Contribution: This study looks at the impressions of current Digital Transformation in pre-existing structures by the people of Bangladesh, and the study proposes a new national health server-centric approach for future solicitation.